PENGARUH EFESIENSI MODAL KERJA DAN SOLVABILITAS TERHADAP PROFITABILITAS - Yeni, Fitri (Jurnal Ekobistek, 2016)
This research was conducted on the Property and Real Estate companies listed on the Indonesian Stock Exchange 2010-2014. This study aims to determine how much influence the Efficiency of working capital (x_1) and Solvency (X_2) partially and jointly to Profitability (Y) using the method of data collection in the form of literature, scientific papers, previous research. The analytical method used is multiple linear regression analysis. Based on the research hypothesis I denied, where Working Capital Efficiency has a value of t <t table (-0.259 <1.688) with a significant level of 0.797> 0.05, meaning a partial no significant effect between Profitability Efficiency Working Capital. Hypothesis 2 received, which has Solvency t> t table (3.258> 1.688) with a significant level of 0.002 <0.05, meaning that there is a partial positive and significant influence between the Solvency Profitability. Simultaneous test (F test) can be seen calculated F value of 6.270 with 2.866 F table so that F count> F table (6.270> 2.866) with significant 0.002 <0.05, then Ho is rejected. This means that there is significant influence between the Efficiency of working capital and solvency to Profitability with multiple linear regression equation is: Y = -2.964 - 0.048 X1 + If the variable Efficiency Working Capital and Solvency its value is zero (0), then the profitability of its value is equal to -2.964. Keywords: Efficiency Working Capital, Solvency and Profitability.